Discovery Assessment and Improvement at an Academic Health Sciences Library: Health Information @ Himmelfarb Five Years Later. Issue 1 (2nd January 2018) - Thompson, JoLinda L.; Sullo, Elaine; Abate, Laura E.; Heselden, Meaghan; Lyons, Kathleen M.
ABSTRACT: Himmelfarb Health Sciences Library was an early health sciences library adopter of web scale discovery with introduction of a customized instance of EBSCO's Discovery Service (EDS) in 2012. After three years with EDS, the library initiated an evaluation project involving two user surveys and a library staff focus group to assess user satisfaction with the service. Resulting changes included introduction of widgets to improve access to clinical content, addition of radio buttons to the search box to make defaults easier to enable and disable, and a custom course reserves search feature. The improvements launched fall semester 2016.